2011
DOI: 10.2134/agronj2010.0490
|View full text |Cite
|
Sign up to set email alerts
|

Seeding Rate, Nitrogen Rate, and Cultivar Effects on Malting Barley Production

Abstract: The malting barley (Hordeum vulgare L.) industry is often challenged by the availability of sufficient volume and quality to meet demand. Our objective was to evaluate the effects of agronomic practices on grain uniformity, protein concentration, yield, and yield components. Field experiments were conducted from 2005 to 2008 at eight rain‐fed locations in western Canada. The effects of two seeding rates (200 and 400 seeds m−2) and five N (0, 30, 60, 90, and 120 kg ha−1) rates on two two‐row barley cultivars (‘… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
92
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(108 citation statements)
references
References 24 publications
12
92
2
Order By: Relevance
“…We hypothesized that the previous crop, rate of nitrogen (N) application, and applying fungicide will impact the producer net return (NR). The quality will be influenced by the previous crop, application of N fertilizer, control of leaf diseases with fungicide, seeding rate, and seeding date (McKenzie et al 2005;O'Donovan et al 2011O'Donovan et al , 2012Turkington et al 2012). Barley yield and grain protein impacts were evident two years after a pulse crop , and barley protein can be increased by late season N application (Bulman and Smith 1993).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We hypothesized that the previous crop, rate of nitrogen (N) application, and applying fungicide will impact the producer net return (NR). The quality will be influenced by the previous crop, application of N fertilizer, control of leaf diseases with fungicide, seeding rate, and seeding date (McKenzie et al 2005;O'Donovan et al 2011O'Donovan et al , 2012Turkington et al 2012). Barley yield and grain protein impacts were evident two years after a pulse crop , and barley protein can be increased by late season N application (Bulman and Smith 1993).…”
Section: Introductionmentioning
confidence: 99%
“…McKenzie et al (2005) found delayed seeding resulted in lower yield but had no impact on protein and plumpness, but O'Donovan et al (2012) found delayed seeding increased grain protein. An increase in seeding rate reduced protein and plumpness, increased kernel uniformity, but reduced yield at seeding rates greater than 300 seed m −2 (McKenzie et al 2005;O'Donovan et al 2011O'Donovan et al , 2012 The impact of the previous year's crop and fungicide application on malting barley returns and risk of returns has not been evaluated. Khakbazan et al (2014) found that barley was more profitable when the crop two years prior was a pulse crop rather than wheat or canola.…”
Section: Introductionmentioning
confidence: 99%
“…Yield and kernel quality can be affected by location, tillage system, cropping sequence and other agronomic practices such as fertilization and disease control (O'Donovan et al, 2011;Sainju et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…The effect of N fertilization on GPC depends on the rate and timing of application, on the crop yield and on the variety seeded (O'Donovan et al, 2011). At very low soil N availability, N fertilization may increase yield without increasing or even slightly decreasing GPC, due to a dilution effect.…”
Section: Introductionmentioning
confidence: 99%
“…A survey of 52 craft breweries in 2001 found that 59% of breweries were interested in using malt that was produced locally (Processing Center, 2001). In the past 15 yr, 30 craft malthouses have opened with the goal of producing unique malts from regionally grown grains (Th omas, 2013;Frank and Meltzer, 2014; Evaluating Barley for the Emerging Craft Malting Industry in Western Washington…”
mentioning
confidence: 99%